Calculation of function for population dynamics model with continuous-time age - Zagorodni, Yu.; Voytenko, V. (Математичне та комп'ютерне моделювання. Серія: Фізико-математичні науки, 2008)
In this article, we present an approach to identify functions in population process model with continuous-time age. The main consideration was given to functions identification of birth, mortality, migration and specific function “becoming mature”. Such functions could be defined analytically or by using specific numeric procedure. A numerical example is given to demonstrate the method, along with computer application to population analysis in Canada and Ukraine.